(untitled) (Journal of Governance and Development (JGD), 2015)
The study assessed the capacity of internal audit units of public sector organizations to enhance good governance. Data for the study was collected through questionnaire sent to chief internal auditors, audit managers and senior managers of public sector organizations. Responses received from respondents were based on a five point scale, ranging from strongly disagree to strongly agree. The study results indicate that internal audit’s ability to ensure better governance is limited by; technical and profession skills set, low motivation, limited spending on IA, and little support for the IA function from management. Other limiting factors include, the issue of independence of the internal auditor which directly impact on IA’s objectivity and indirectly may influence which audit gets performed as planned.